Hikmah pedagogy: promoting open-mindedness, tolerance and respect for others' religious views in classrooms - Hussien, Suhailah; Hashim, Rosnani; Mohd. Mokhtar, Nazatul Akmar (Sense Publishers, 2017)
Ensuring good relations among the different races, ethnics and religions is one of the primary aims of a multiracial and religious country like Malaysia. This forms the basis of a harmonious and successful nation, where education is the avenue to achieve this aim.